Mediterranean frontiers borders, conflict and memory in a transnational world - Bechev, Dimitar; Nicolaidis, Kalypso (Library of international relations, 2010)
The identity of any nation-state is inextricably linked with its borders and frontiers. Borders connect nations and sustain notions of social cohesion. Yet they are also the sites of division, fragmentation and political conflict. This study examines the emergence of state borders and polarised identities in the Mediterranean.